A Novel Treatment Concept for Advanced Stage Mandibular Osteoradionecrosis Combining Isodose Curve Visualization and Nerve Preservation: A Prospective Pilot Study - van Baar, Gustaaf J. C.; Leeuwrik, Lars; Lodders, Johannes N.; Liberton, Niels P. T. J.; Karagozoglu, K. Hakki; Forouzanfar, Tymour; Leusink, Frank K. J. (Frontiers in Oncology, 2021)
Background Osteoradionecrosis (ORN) of the mandible is a severe complication of radiation therapy in head and neck cancer patients. Treatment of advanced stage mandibular osteoradionecrosis may consist of segmental resection and osseous reconstruction, often sacrificing the inferior alveolar nerve (IAN). New computer-assisted surgery (CAS) techniques can be used for guided IAN preservation and 3D radiotherapy isodose curve visualization for patient specific mandibular resection margins. This study introduces a novel treatment concept combining these CAS techniques for treatment of advanced stage ORN. Methods Our advanced stage ORN treatment concept includes consecutively: 1) determination of the mandibular resection margins using a 3D 50 Gy isodose curve visualization, 2) segmental mandibular resection with preservation of the IAN with a two-step cutting guide, and 3) 3D planned mandibular reconstruction using a hand-bent patient specific reconstruction plate. Postoperative accuracy of the mandibular reconstruction was evaluated using a guideline. Objective and subjective IAN sensory function was tested for a period of 12 months postoperatively. Results Five patients with advanced stage ORN were treated with our ORN treatment concept using the fibula free flap. A total of seven IANs were salvaged in two men and three women. No complications occurred and all reconstructions healed properly. Neither non-union nor recurrence of ORN was observed. Sensory function of all IANs recovered after resection up to 100 percent, including the patients with a pathologic fracture due to ORN. The accuracy evaluation showed angle deviations limited to 3.78 degrees. Two deviations of 6.42° and 7.47° were found. After an average of 11,6 months all patients received dental implants to complete oral rehabilitation. Conclusions Our novel ORN treatment concept shows promising results for implementation of 3D radiotherapy isodose curve visualization and IAN preservation. Sensory function of all IANs recovered after segmental mandibular resection.